Launching IFMBE into the 21st Century: 50 Years and Counting - Voigt, Herbert; Magjarevic, Ratko (Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book has been created for the 50th anniversary of the International Federation for Medical and Biological Enineering and Computing IFMBE. The IFMBE is primarily a professional organization of national and transnational societies representing interests in medical and biological engineering. In six parts, this book presents an overview on the federation, its activities and the characters who shaped IFMBE. In the last part, all member societies giveÂ  a short presentation.